Addressing Challenges to Building Resilience Through Interdisciplinary Research and Engagement. Issue 7 (27th September 2018) - Berke, Philip R.; Quiring, Steven M.; Olivera, Francisco; Horney, Jennifer A.
Abstract: Resilient communities are less affected by, and recover faster from, natural disasters. To be resilient in rapidly changing contemporary environments subject to the effects of complex factors such as climate change and urbanization, communities must effectively and efficiently adapt to new conditions to minimize future risks. To develop resilience, the hazards to which the community is exposed and vulnerable (i.e., future hurricanes, subsidence, salt water intrusion) must be accurately assessed, the systems (i.e., natural, built, and social) must be well understood, and the community must be engaged in the proactive planning and priority setting process. An approach to building resilience that utilizes the adaptive capacity of planning highlights opportunities to work collaboratively across disciplines to incorporate models and data from different disciplines to reduce uncertainty. We present one interdisciplinary group's approach to addressing challenges to building resilience through proactive planning, including: (1) characterizing hazards more accurately; (2) improving understanding of the vulnerability of natural (e.g., climate and infrastructure) systems subject to hazards; and (3) capturing potential synergies from interactions between planning and policies that govern decisions about the design of human settlements in hazardous areas.